Sizing of a retaining structure in a wall reinforced with geosynthetics (Research, Society and Development, 2021)
Taking advantage of embankments with steep slopes and great heights often means adopting more elaborate solutions, such as the application of geosynthetics in reinforced walls. This article presents the dimensioning of a wall reinforced with geosynthetic for stabilization of a slope located in the area of the Jordão Reservoir, Recife - Pernambuco, in order to alter the initial design of containment in gabion wall of the same embankment. The dimensioning of the reinforced wall is carried out considering the criteria in the analysis of the external and internal stability of the structure, and the proposal for alteration in the initial surface drainage project is also indicated so that the slope stability. In the analysis of external stability, there was a reinforcement length of 5,86 m, which met both the slip and tip safety factor. In the analysis of internal stability using the Jewell method (1991), a reinforcement length of 5,28 m was obtained. Then, adopting the longest reinforcement length among the results of the analyzes, obeying the minimum lengths required in all stability criteria. The results obtained showed that the wall reinforced with geosynthetic for stabilization of the slope Laser Electro and the geotechnical and geometric parameters involved were adequate to the project, being a safe solution for faces of the walls or more vertical slopes.